2005
DOI: 10.2190/0373-6757-jq16-8513
|View full text |Cite
|
Sign up to set email alerts
|

Mother-Father Concordance on Treatment Choices in the Care of Sick Children under Five Years of Age in Osun State, Nigeria

Abstract: Communication and agreement between spouses has been found to be an important factor in terms of acceptance and use of family planning services and supplies. Therefore, it is likely that agreement between spouses may play an important role in other aspects of family health, including care of childhood illness. This study, based in a rural and an urban community in Osun State, Nigeria, set out to determine the agreement between mothers and fathers on the illness experience and care provided to their preschool a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
10
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 13 publications
3
10
0
Order By: Relevance
“…Similar to other studies, we found that mothers are most frequently the first ones to identify illness symptoms (23), but that a mother often does not have the agency or resources to seek care herself and must consult her husband or in-laws prior to seeking care outside the home (16) and decisions about where and when to seek care for a child are often taken by fathers, since men are considered to be responsible for family resources and pay for care (8,19,30). We identified some variation across LGAs with regard to making use of community based treatment options.…”
Section: Enabling Factors To Seeking Care For Sick Children Outside Tsupporting
confidence: 91%
See 1 more Smart Citation
“…Similar to other studies, we found that mothers are most frequently the first ones to identify illness symptoms (23), but that a mother often does not have the agency or resources to seek care herself and must consult her husband or in-laws prior to seeking care outside the home (16) and decisions about where and when to seek care for a child are often taken by fathers, since men are considered to be responsible for family resources and pay for care (8,19,30). We identified some variation across LGAs with regard to making use of community based treatment options.…”
Section: Enabling Factors To Seeking Care For Sick Children Outside Tsupporting
confidence: 91%
“…Additionally, our review of numerous studies of care seeking in Nigeria found that the majority focused on fever and malaria (12,21,22) and did not examine care seeking across the other, common child illnesses such as pneumonia and diarrhea. The majority of the existing studies were quantitative (16,18,23) and did not provide adequate depth into the multiple factors that influence sick-child care seeking, including complex gender and social norms.…”
Section: Introductionmentioning
confidence: 99%
“…Recent DHS data [2] indicate that only 64% of pregnant Nigerian women receive antenatal care; 39% are delivered by a skilled birth attendant; while only 35% of women give birth in a health facility. Similarly, Nigeria has one of the lowest rates of childhood immunization [2], while most families rely on unproven traditional methods for treatment of major childhood illnesses [8].…”
Section: Introductionmentioning
confidence: 99%
“…The social workers' department efforts at organizing counselling sessions and home visits for every case of registered child abuse were rewarded when many fathers who abandoned their wives with the babies were reunited and many abandoned children rehabilitated. These parents/caregivers became cooperative and participated in nursing the children 25 , although mortality was high due to irreversible complications of the neglected primary surgical pathology.…”
Section: Discussionmentioning
confidence: 99%